Michèle Roberts’s "Flesh and Blood" as an Example of "Écriture Feminine" - Morawska, Joanna (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2022)
The essay offers an analysis of Flesh and Blood, a novel by Michèle Roberts, first published in 1994. It discusses the book from the vantage point of French feminist criticism, especially écriture feminine, as well as gynocritics. The theory serves as a reference point for a better understanding of the novel’s structure, language and plot. In the opening paragraphs, the essay delineates the main premises of écriture feminine, a French feminist theory represented primarily by Hélène Cixous and Luce Irigaray, and gynocritics, a concept developed by the American feminist scholar Elaine Showalter. It then moves on to portray Flesh and Blood as an example of écriture feminine, analysing the aspects of the novel that mirror the theories of the French feminist critics: characters, motifs, structure, formal ploys and language.